Beginning of the Cosmos in the Light of Philosophy and Cosmology - Rahman, Atikur; Roshlan Rahman Dipto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The question of whether the cosmos has a finite beginning or an infinite past remains a central issue in both philosophy and contemporary cosmology. This study investigates the metaphysical and physical plausibility of a past-eternal universe by integrating philosophical analysis with conceptual examination of modern cosmological models. Employing qualitative philosophical methodology and critical analysis of theoretical physics, the paper evaluates temporal ontology (A-theory and B-theory), the implications of special relativity, and paradoxes associated with actual infinities, including Thomson’s Lamp and a formalized infinite traversal analogy. The analysis argues that an actual infinite temporal regress generates logical and metaphysical difficulties, particularly under a dynamic conception of temporal becoming. Furthermore, the paper examines the Friedmann–Lemaître–Robertson–Walker model, the Hawking–Penrose singularity theorems, and the Borde–Guth–Vilenkin theorem, assessing their implications for past completeness. While certain speculative models attempt to avoid a temporal boundary, they remain mathematically constrained and philosophically contentious. The study concludes that both metaphysical reasoning and contemporary cosmology provide convergent support for the thesis that the cosmos is temporally finite and had a definite beginning.